Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/ijerph120404214
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Polyacrylamide-Degrading Bacteria from Dewatered Sludge

Abstract: Polyacrylamide (PAM) is a water-soluble polymer that is widely used as a flocculant in sewage treatment. The accumulation of PAM affects the formation of dewatered sludge and potentially produces hazardous monomers. In the present study, the bacterial strain HI47 was isolated from dewatered sludge. This strain could metabolize PAM as its sole nutrient source and was subsequently identified as Pseudomonas putida. The efficiency of PAM degradation was 31.1% in 7 days and exceeded 45% under optimum culture condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 37 publications
5
68
0
Order By: Relevance
“…The results showed that the strain could utilize HPAM as their only carbon source and nitrogen source, and the same condition had also been described by Bao et al [18], Wei et al [19] and Yu et al [20] with HPAM removal rates of 33.7%, 48.5% and 56.8%, respectively. Compared with Wang et al [21] degraded hydrolyzed polyacrylamide by the single ozonation and removal rates of TOC and HPAM reached 37.1% and 83.4%, immobilized R2 had higher removal efficiency of TOC and slightly lower one of HPAM.…”
Section: Comparison Between Hpam Biodegradation By Free Strain R2 Andsupporting
confidence: 83%
See 1 more Smart Citation
“…The results showed that the strain could utilize HPAM as their only carbon source and nitrogen source, and the same condition had also been described by Bao et al [18], Wei et al [19] and Yu et al [20] with HPAM removal rates of 33.7%, 48.5% and 56.8%, respectively. Compared with Wang et al [21] degraded hydrolyzed polyacrylamide by the single ozonation and removal rates of TOC and HPAM reached 37.1% and 83.4%, immobilized R2 had higher removal efficiency of TOC and slightly lower one of HPAM.…”
Section: Comparison Between Hpam Biodegradation By Free Strain R2 Andsupporting
confidence: 83%
“…and Yu et al . with HPAM removal rates of 33.7%, 48.5% and 56.8%, respectively. Compared with Wang et al .…”
Section: Resultsmentioning
confidence: 99%
“…High molecular weight polymer chains are degraded by microbes into monomeric and oligomeric units to enable assimilation [43]. Native soil bacteria ( Pseudomonas, Xanthomonas, Rhodococcus, Klebseilla ) have been found to degrade and utilize polyacrylamide (PAM) as sole source of C and N under both aerobic and anaerobic conditions [27, 28, 43, 44]. They secrete PAM-specific extracellular amidase ( amidohydrolase ) enzyme to hydrolyse the amide group into acrylic acid and ammonia, according to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study has shown that molecular weights above 3 Â 10 3 Da are recalcitrant to microbial mineralization (El-Mamouni et al, 2002). In addition, although Bacillus (Bao et al, 2010), Acinetobacter (Matsuoka et al, 2002), Pseudomonas (Yu et al, 2015), and Clostridium (Ma et al, 2010) grew in the four reactors, their abundances were low. Thus, further studies are required to investigate the mineralization conditions of PAM.…”
Section: Discussionmentioning
confidence: 79%